Effects of Local Microorganisms and Variety Interaction on Growth, Yield, and Fruit Quality of Melon (Cucumis melo L.) - Anita Hazimah Putri; Jon Yawahar (University of Prof. Dr. Hazairin, SH, 2026)
The increasing demand for melons has not been accompanied by a proportional increase in production. This study was conducted from January to April 2024 in Kandang Limun, Bengkulu, Indonesia, and aimed to evaluate the most suitable melon varieties and types of local microorganisms (MOL) to improve plant growth, yield, and fruit quality. The experiment was arranged in a factorial Completely Randomized Design (CRD) with two factors: three melon varieties (Gracia, Sonya, and Tavia) and four MOL treatments (MOL from stale rice, papaya MOL, bamboo shoot MOL, and a control without MOL). These factors produced 12 treatment combinations, each replicated three times, resulting in 36 experimental units and a total of 108 plants. The results showed a significant interaction between melon varieties and MOL types on fruit diameter, sweetness, and hardness. The largest fruit diameter (15,2 cm) was obtained from the Tavia variety treated with papaya MOL. The highest fruit sweetness (11,9 oBrix) was observed in the Sonya variety with papaya MOL, while the highest fruit hardness (3,2 kg cm-2) was recorded in the Gracia variety without MOL. Overall, the Tavia variety exhibited the best performance in terms of growth, yield, and fruit quality. Among the treatments, papaya MOL showed the most favorable effect, particularly in enhancing fruit diameter and sweetness.